2013
DOI: 10.1262/jrd.2013-023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Herpesviruses (HHVs) in Semen of Human Male Infertile Patients

Abstract: Recently we demonstrated an ectopic expression of the human herpesvirus 1 thymidine kinase (HHV1-TK) gene by functioning of an intrinsic endogenous promoter in the transgenic rat (TG-rat), suggesting that HHV1 infection in humans induces expression of the TK gene with the ectopic promoter in the testis and results in accumulation of HHV1-TK protein, triggering male infertility similar to that in the TG-rat. Hence, in this study, we started to investigate a relationship between infection of herpesvirus and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Recently, a number of studies have detected HHVs in the semen and/or spermatozoa of ∼90% of infertile male patients, although regional variations must be taken into account (Table 2) [6,[9][10][11][21][22][23][24][25][26][27][28][29][30][31]. Many investigators have tried to confirm the relationship between male infertility and HHVs infection by combining viral infection rates with statistical analysis of semen and/ or sperm samples derived from PCR-based viral DNA analysis, antigen-antibody reaction, and immunocytochemistry of spermatozoa.…”
Section: Herpesviridae 78mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a number of studies have detected HHVs in the semen and/or spermatozoa of ∼90% of infertile male patients, although regional variations must be taken into account (Table 2) [6,[9][10][11][21][22][23][24][25][26][27][28][29][30][31]. Many investigators have tried to confirm the relationship between male infertility and HHVs infection by combining viral infection rates with statistical analysis of semen and/ or sperm samples derived from PCR-based viral DNA analysis, antigen-antibody reaction, and immunocytochemistry of spermatozoa.…”
Section: Herpesviridae 78mentioning
confidence: 99%
“…Analysis of oligozoospermia rates between viral DNA-negative (36 patients) and -positive (39 patients) according to WHO Guidelines (5th edition). Reproduced and modified from [21] with permission from the Society for Reproduction and Development.…”
Section: Hhv-1-tk In Human Testismentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies report a prevalence of approximately 6% in men from Germany, North America, France, Africa, Greece, Denmark, Australia, and Russia (Table 1). In contrast, several studies on semen of fertility-clinic attendants from China, Taiwan, Spain, and Greece, have reported high prevalences of HCMV between 21.6% to 56.9% [14,22,23,38,40]. This could possibly be explained by geographic variation, however another study from Greece, also of semen from fertility-clinic attendants, found HCMV in only 7.1% [17].…”
Section: Introductionmentioning
confidence: 96%
“…Bezold et al found the prevalence to be 4.0% in a German population of infertility patients [11] and 3.7% in a population of American infertility patients [12]. Chen et al found HHV-6A/B in 2.0% of infertility patients from China [14], whereas Michou et al detected HHV-6A/B in 8.2% of 109 men from couples undergoing IVF treatment in Spain [22]. A slightly higher prevalence of 13.5% was seen by Kaspersen et al in semen from Danish sperm donors [18] (Table 2), suggesting that the prevalence of HHV-6A/B is not increased among patients attending a fertility clinic.…”
Section: Introductionmentioning
confidence: 99%